Neuroactive steroids, mood stabilizers, and neuroplasticity: alterations following lithium and changes in Bcl-2 knockout mice - Marx, Christine E.; Yuan, Peixiong; Kilts, Jason D.; Madison, Roger D.; Shampine, Lawrence J.; Manji, Husseini K. (The international journal of neuropsychopharmacology, 2008)
Many neuroactive steroids (NS) demonstrate neurotrophic and neuroprotective actions, including protection against apoptosis via Bcl-2 protein. NS are altered in post-mortem brain tissue from subjects with bipolar disorder, and several agents with efficacy in mania elevate NS in rodents. We therefore hypothesized that lithium and valproate may elevate NS, and compensatory NS increases may occur in Bcl-2 knockout mice. NS levels (allopregnanolone, pregnenolone) were determined in frontal cortex by negative ion chemical ionization gas chromatography/mass spectrometry in male Wistar Kyoto rats treated chronically with lithium, valproate, or vehicle. NS were also investigated in heterozygous Bcl-2 knockout mice. Allopregnanolone levels are significantly elevated in lithium-treated (p<0.05), but not in valproate-treated, rats. Pregnenolone levels also tend to be higher following lithium treatment (p=0.09). Knockout of Bcl-2 significantly increases pregnenolone levels in mice (p<0.01), while allopregnanolone levels are unaltered. NS induction may be relevant to mechanisms contributing to lithium therapeutic efficacy and neuroprotection.